BRAF mutational analysis in ovarian tumors: recent perspectives - Wong KK; Tsai CC; Gershenson DM (Dove Medical Press, 2015)
Kwong-Kwok Wong,1 Ching-Chou Tsai,2 David M Gershenson11Department of Gynecologic Oncology and Reproductive Medicine, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 2Department of Obstetrics and Gynecology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, Taiwan, Republic of ChinaAbstract: BRAF mutations are rare in ovarian cancer and mainly occur in indolent serous borderline tumors (SBTs), also known as serous tumors of low malignant potential or atypical proliferative serous tumors. The reported percentage of BRAF mutations in SBTs varies from 23% to 71%. Although a high percentage of stage II–IV SBTs with noninvasive implants have progressed to invasive low-grade serous carcinomas when patients were observed for 5 years or longer, BRAF mutations are rare in low-grade serous carcinomas as well as in invasive implants associated with SBTs. BRAF mutations in SBTs may prevent SBTs from progressing to invasive carcinomas. On the other hand, the reported percentage of BRAF mutations in mucinous carcinoma (20%) is much higher than that of mucinous borderline tumor (5%). Further investigation of the role of BRAF mutations in SBTs and mucinous tumor will shed light on the molecular mechanism underlying the role of BRAF mutations in tumor progression in different cellular context and the clinical utility of BRAF mutations in SBTs as a biomarker of favorable prognosis.Keywords: BRAF V600E, ovarian cancer, COLD-PCR